Assessment of Low Birth Weight and Associated Factors Among Neonates in Butajira General Hospital, South Ethiopia, Cross Sectional Study, 2019 - Tigistu Toru; Walellign Anmut (International Journal of Pediatrics)
Background. Low birth weight is defined as when a newborn weighs less than 2,500 grams within an hour of birth. Globally, it has been known that around 15.5% of newborns were below the normal level of weight at their birth and 95% of these infants lived in developing countries. The main objective of this study was to assess the prevalence and associated factors of low birth weight among newborns delivered at Butajira General Hospital, Southwest Ethiopia. Methods. An institutional-based cross-sectional study design was employed. All 196 paired study participants (newborn-mother) who were born on a one-month duration of the data collection period were included in the study. A pretested questionnaire was used to gather pertinent information about mother and newborn along with measuring newborn birth weight. Result. Majority of mothers 175 (92.1%) were aged between 20 and 34 years, and 186 (97.9%) were married. About 169 (88.9%) were protestant religion followers. This study showed that the magnitude of low birth weight among study participants was 12.5%, and factors such as maternal medical complication during pregnancy, maternal MUAC less than 23 cm, and birth interval less than 24 months were significantly associated with low birth. Conclusion. The study finding indicated that a significant number of newborns measured underweight which is below the normal level of weight at birth. The study identified factors such as maternal medical condition during pregnancy, maternal MUAC less than 23 cm, and birth interval less than 24 months. Based on study findings, we recommend health care officials, policymakers, key persons in the family, and volunteers to work on nutritional values particularly during pregnancy and before pregnancy. Spacing of birth is crucial to have healthy baby and healthy family even healthy society at large, so attention should be paid on family planning utilization.